Digital cold panniculitis: A winter malady! - Das, Prarthana; Neibeituo, Dominic Belho (Indian Journal of Child Health, 2024)
The panniculitides include a group of heterogeneous disorders of varied aetiology that manifest as inflamed nodules in the subcuta-neous tissue. Few forms of panniculitis namely subcutaneous fat necrosis exclusively affects newborns whereas other types affects adults and paediatric group equally. These lesions may appear secondary to some systemic illness or following external insult. We report a child presenting with panniculitis lesion involving all the digits of his hands following exposure to cold.